Climate Change Impacts, Agro-Ecosystem Stress, and Adaptive Agricultural Strategies in South Asia: A Scopus Bibliometric Analysis (1997–2026) - Dipika Biswas (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study presents a bibliometric analysis of research on climate change impacts, agro-ecosystem stress, and adaptive agriculture in South Asia from 1997 to 2026. Initially, 2,260 documents were retrieved mainly from the Scopus database, and 1,580 documents were selected after applying predefined screening criteria. Using bibliometric and informatics-based analytical tools, the study examines publication trends, collaboration networks, influential contributors, and thematic evolution in the field. The findings reveal a significant increase in scholarly output, particularly after 2015, indicating growing regional and global concern over climate-induced agricultural challenges. Keyword analysis highlights the dominance of climate change, drought, and resilience, reflecting a strong focus on ecological vulnerability, food security, and livelihood sustainability. Country-level analysis shows that India leads research production, followed by Pakistan, Bangladesh, and China. Major thematic clusters include climate resilience, sustainable agriculture, food security, and environmental stress management. Despite this growth, gaps remain in the integration of information systems, interdisciplinary collaboration, and region-specific adaptation strategies. This study provides a structured overview of the intellectual landscape and offers useful insights for researchers, policymakers, and practitioners working toward climate-resilient and sustainable agriculture in South Asia.